Activation of Resolution Pathways to Prevent and Fight Chronic Inflammation: Lessons From Asthma and Inflammatory Bowel Disease - Barnig, Cindy; Bezema, Tjitske; Calder, Philip C.; Charloux, Anne; Frossard, Nelly; Garssen, Johan; Haworth, Oliver; Dilevskaya, Ksenia; Levi-Schaffer, Francesca; Lonsdorfer, Evelyne; Wauben, Marca; Kraneveld, Aletta D.; et al. (Frontiers in Immunology, 2019)
Formerly considered as a passive process, the resolution of acute inflammation is now recognized as an active host response, with a cascade of coordinated cellular and molecular events, that promotes termination of the inflammatory response and initiates tissue repair and healing. In a state of immune fitness, the resolution of inflammation is contained in time and space enabling the restoration of tissue homeostasis. There is increasing evidence that poor and/or inappropriate resolution of inflammation participates in the pathogenesis of chronic inflammatory diseases, extending in time the actions of pro-inflammatory mechanisms, and responsible in the long run for excessive tissue damage and pathology. In this review, we will focus on how resolution can be the target for therapy in ‘Th1/Th17 cell-driven’ immune diseases and ‘Th2 cell-driven’ immune diseases, with inflammatory bowel diseases and asthma, as relevant examples. We describe the main cells and mediators stimulating the resolution of inflammation and discuss how pharmacological and dietary interventions but also life style factors, physical and psychological conditions, might influence the resolution phase. A better understanding of the impact of endogenous and exogenous factors on the resolution of inflammation might open a whole area in the development of personalized therapies in non-resolving chronic inflammatory diseases.